The Impact of Dietary Fiber on Cardiovascular Disease Prevention and Management: A Systematic Review and Meta-Analysis - Patel, Rutvij; Elamin, Ahmed Elfatih; Hack, Sarah; Ryali, Niharika; Virk, Ghazala S.; Ahmed, Masood; Ahmed, Zubair; Abid, Marium; Hassan, Mohammad Saad; Ugripelli, Venkata Avinash; Mirza, Muhammad Sohail S. (Cardiology and Cardiovascular Medicine, 2025)
The purpose of this systematic review and meta-analysis was to determine the effects of dietary fiber intake on cardiovascular health outcomes including the incidence, mortality, lipids and blood pressure. A random effects model was used to analyze a total of eight eligible studies, including randomized controlled trials and prospective cohort studies, to take into account heterogeneity in study populations, fiber types and outcome definitions. Higher dietary fiber intake was significantly associated with reduced cardiovascular diseases (CVDs) mortality (pooled HR 0.75–0.82), reduced incidence of CVD events, reductions in systolic blood pressure (≤3.5 mmHg) and meaningful reductions in Low-Density Lipoprotein (LDL)Cholesterol (≤0.30 mmol/L). Our findings also showed moderate heterogeneity (I² = 30–56%) however protective effects overall were consistent by study type and endpoints. These benefits are mechanistically linked to changes in lipid metabolism, insulin sensitivity, inflammation and metabolites derived from gut microbiota, including short chain fatty acids. The strong evidence notwithstanding, global fiber intake is below recommended levels where public health interventions and clinical dietary guidance promoting fiber-rich foods are needed. Results from these studies support a role of dietary fiber in primary prevention of cardiovascular disease and in the management of patients with atherosclerosis.